The Transformation of the Midah Archetype: The Dynamics of Femininity and the Process of Individuation in Tere Liye's Novels "Pulang" and "Novel Pergi" - Irma Rismawati; Asep Nurjamin; Lucky Rahayu Nurjamin; Yustika Nurfajriah; Ari Kartini (Journal of Innovation and Research in Primary Education, 2026)
Female characters in contemporary Indonesian fiction have increasingly served as sites of complex psychological and symbolic meaning, yet their archetypal dimensions remain insufficiently theorized within the existing scholarship. This study employs a qualitative descriptive-interpretive design with content analysis to examine the character of Midah in Tere Liye's novels Pulang (2015) and Pergi (2018), drawing on Carl Gustav Jung's theory of archetypes and the collective unconscious as its theoretical framework. The analysis reveals that Midah embodies a triadic archetypal structure comprising The Great Mother — expressed through moral counsel, emotional constancy, and transcendental protection; the Anima — manifested through silent, healing mediation; and The Self — constituted through her symbolic positioning as the ultimate destination of the main character Bujang's individuation. Notably, Midah's archetypal identity evolves dynamically across both novels in correspondence with Bujang's advancing psychological development. These findings extend prior scholarship on female archetypes in Tere Liye's works and demonstrate that Midah represents a more spiritually autonomous and psychically complex maternal figure than those identified in previous studies or found in canonical Indonesian literary tradition. This study contributes to Indonesian literary psychology by establishing a replicable model for Jungian archetypal analysis of female characters and affirming that Jung's theoretical framework can be productively applied to contemporary Indonesian fiction while remaining attentive to its distinctive cultural and spiritual values.